ANALISIS TEKUK LATERAL BALOK DENGAN METODE ELEMEN HINGGA - MURNI DEWI, SRI
In this thesis lateral buckling of non-prismatic beam with non-uniform load are analysed by the finite element method. A computer program for both bifurcation and non-bifurcation buckling are developed. The results for prismatic beam with uniform load are compared with those solution are known. Example problems are given for four selected variable ie.: non-prismatic beam, non-uniform load, beam with intermediate restraints, and beam with intermediate torsion.